Plastid and nuclear DNA marker data support the recognition of four tetraploid marsh orchids (Dactylorhiza majalis s.l., Orchidaceae) in Britain and Ireland, but require their recircumscription - Hedrén, Mikael; Olofsson, Sofie; Bateman, Richard M. (Biological Journal of the Linnean Society, 2011)
Relationships among allotetraploid marsh orchids collectively assignable to Dactylorhiza majalis s.l. are exceptionally complex because of multiple origins, secondary hybridization with each other, and with their parental lineages, local adaptation, and genomic reorganization processes, all extending through time and space. We sampled 34 populations from Britain and Ireland in an attempt to simultaneously interpret patterns of genetic differentiation within and between populations. The material analysed consisted of 250 individuals that were examined for variation at five nuclear microsatellite loci, internal transcribed spacer (ITS), and plastid DNA. Once integrated, patterns of differentiation in the three molecular data sets show that the British and Irish members of the D. majalis s.l. complex should be assigned to a minimum of four genetically differentiated subgroups of equal status (either species or subspecies), broadly corresponding to the traditional D. majalis ssp. praetermissa, ssp. purpurella, ssp. occidentalis, and ssp. traunsteinerioides. UK plants previously attributed to 'Dactylorhiza lapponica' and given high conservation status have been shown to be genetically identical to ssp. traunsteinerioides. The endemic Hebridean marsh orchid, D. majalis ssp. ebudensis, genetically resembles ssp. traunsteinerioides. Dactylorhiza majalis 'ssp. cambrensis' could readily be accommodated within ssp. purpurella. Together, these observations reinforce a recent assertion that anthocyanin content has been over-weighted in previous morphologically based classifications of Dactylorhiza. Several study populations showed signs of hybridization and introgression with other allotetraploids, or their parental lineages, especially with D. incarnata s.l. However, ssp. praetermissa and ssp. traunsteinerioides were better separated than anticipated: southern populations widely regarded as mixed populations of the two taxa are arguably better treated as containing an unusually narrow-leaved, ecologically specialized form of ssp. praetermissa. Accepting this recircumscription means that the southern margins of the distributions of ssp. purpurella and ssp. traunsteinerioides now coincide, stretching from mid-Wales to the Humber Estuary of Yorkshire, and together indicating a significant genetic transition zone. Plastid haplotype data confirm that ssp. traunsteinerioides and ssp. praetermissa are relatively old polyploids derived from the Continental D. majalis s.l. complex, whereas ssp. purpurella and ssp. occidentalis may have more recent (most likely postglacial) origins within their current distributions. (C) 2011 The Linnean Society of London, Biological Journal of the Linnean Society, 2011, 104, 107-128.
Keywords: classification; genetic structure; hybridization; introgression; ITS; microsatellites; polyploidy; taxonomic circumscription